Rapid prototyping of flexible crystal models - Tan, Malcolm Yong Liang. (2009)
Crystalline minerals have many interesting properties, and many of these properties have useful applications. By studying the minerals’ crystal structures, their properties and behaviors, can be better understood and appreciated.